Development of methods for the analysis of functional requirements to an information system for consistency and illogicality - Ievlanov, M.; Vasiltcova, N.; Panforova, I. (My University, 2018)
The order of work aimed at analyzing the requirements is considered, taking into account application of the service approach to development of IS, models and methods of development of representations of functional requirements to IS at the knowledge level. It was proposed to perform work on IS requirements analysis in parallel to the work on the requirements development. Such an organization of work makes it possible to reduce the time required to perform work on the IS macro design. Methods of analysis of separate frames and relations between frames and between frames and interfaces of representations of functional requirements to IS at the knowledge level were developed. The essence of the methods lies in comparison of frames and relations, used for description of concepts and terms in a subject area. These methods make it possible to detect inconsistencies, caused by attempts to describe the same object in a subject area in different ways. The indicator of illogicality of the stated functional requirement and the method of detection of illogical functional requirements was developed. The essence of this method lies in identification of separate branches of the frame hierarchy (ontological points) that are present in representation of only one functional requirement to IS. Such requirement is not related to other functional requirements to IS and is considered to be illogical. This method makes it possible to assess a degree of illogicality of each functional requirement, based on which it is possible to make a decision about the feasibility of IS development. The research contains an example of testing the developed methods in the analysis of functional requirements to the project related to the functional labor safety module. Розглянуто задачу розробки методів аналізу сформульованих функціональних вимог до інформаційної системи. Запропоновані методи дозволяють виявляти протиріччя між описами окремих фреймів, інтерфейсів та зв’язків у представленнях вимог на рівні знань та нелогічність описів функціональних вимог. Використання даних методів дозволяє скоротити час розробки інформаційної системи за рахунок виконання робіт з аналізу вимог паралельно роботам з формування вимог. Рассмотрена задача разработки методов анализа сформулированных функциональных требований к информационной системе. Предложенные методы позволяют выявлять противоречия между описаниями отдельных фреймов, интерфейсов и связей в представлениях требований на уровне знаний и нелогичность описаний функциональных требований. Использование данных методов позволяет сократить время разработки информационной системы за счет выполнения работ по анализу требований параллельно работам по формированию требований.
Keywords: Requirements analysis; functional requirements; frame; inconsistency; illogicality; ontological point